DEVELOPMENT OF PHYSICS LEARNING MATERIALS BASED ON GUIDED INQUIRY MODEL INTEGRATED WITH VIRTUAL LABORATORY TO FACILITATE STUDENT’S SCIENTIFIC ARGUMENTATION ABILITY - Ahmad Fauzi Hendratmoko; Wasis Wasis; Endang Susantini (Universitas Pendidikan Mandalika, 2016)
The purpose of this research is to develop physics learning materials based on guided inquiry model integrated with virtual laboratory to practice student’s scientific argumentation skill. This research uses 4D development model and tested in 91 students, divided into three classes, X MIPA 1, X MIPA 2, and X MIPA 3 SMA Senopati Sedati with try out design using one group pretest-posttest design. The learning instruments developed are: (a) syllabus (b) lesson plan, (c) student’s book, (d) student worksheet, and (e) test of students’ scientific argumentation skill. The Research data gotten through validation method, observation, test, and questionnaire. The research result was analyzed descriptively quantitative and qualitative. The students’ scientific argumentation skill was analyzed with n-gain. The research result gotten are (a) the learning instruments developed categorized as very valid, (b) the learning activity was well done, (c) the students’ scientific argumentation skill run into enhancement in middle categorized, and (d) the students responded very positively to the learning that is already implemented. Based on analysis result and discussion, it can be concluded that the physics learning material guided inquiry model integrated with virtual laboratory developed is worthy to be used to practice students’ scientific argumentation skill.